Creativity/Anthropology - Lavie, Smadar; Narayan, Kirin; Rosaldo, Renato (Cornell University Press, 1993)
Creativity and play erupt in the most solemn of everyday worlds as individuals reshape traditional forms in the light of changing historical circumstances. In this lively volume, fourteen distinguished anthropologists explore the life of creativity in social life across the globe and within the study of ethnography itself. Contributors include Barbara A. Babcock, Edward M. Bruner, James W. Fernandez, Don Handelman, Smadar Lavie, José E. Limon, Barbara Myerhoff, Kirin Narayan, Renato Rosaldo, Richard Schechner, Edward L. Schieffelin, Marjorie Shostak, Anna Lowenhaupt Tsing, and Edith Turner.